A Prenylated Flavonoid from the Methanol Fraction of Breadfruit Root (Artocarpus communis) - Kristina Damiyanti; Ari Widiyantoro; Rudiyansyah Rudiyansyah (Jurnal Akademika Kimia, 2020)
Breadfruit (Artocarpus communis) is a tropical fruit plant that belongs to the genus Artocarpus of the Moraceae family. Prenylated flavonoid compounds were isolated from the methanol fraction of breadfruit root wood using maceration, partitioning, and chromatography methods, while characterization was carried out through phytochemical tests and 1H-NMR spectrum data analysis. The K1D2 (P1) compound obtained was a yellow solid with a mass of 5 mg. The phytochemical test of the K1D2 (P1) compound gave positive results for the flavonoid group. The 1H-NMR spectrum data (CDCl3, 500 MHz) of compound K1D2 (P1) showed a typical chemical shift at δH 13.42 (1H, s, 5-OH) for the hydroxy groups associated with carbonyl; 7.68 (1H, d, J = 8.5 Hz, H-6 ′); 6.71 (1H, dd, J = 16.0; 7.1 Hz, H-10); 6.56 (1H, d, J = 16.0 Hz, H-9); 6.54 (1H, dd, J = 8.5; 1.8 Hz, H-5 ′); 6.46 (1H, s, H-3); 6.42 (1H, d, J = 1.8 Hz, H-3 ′); 6.26 (1H, d, J = 9.3 Hz, H-14); 5.42 (1H, d, J = 9.3 Hz, H-15); 3.94 (3H, s, 2′-OCH3); 2.47 (1H, m, H-11); 1.97 (3H, s, H-17); 1.69 (3H, s, H-18), and 1.10 (6H, d, J = 6.7 Hz, H-12 and H-13). Based on the results of phytochemical tests and analysis of 1H-NMR spectrum data compared with literature data, it showed that the isolated K1D2 (P1) compound is 4 ′, 5-dihydroxy-6,7- (2,2-dimethylpirano) -2'-methoxy- 8γ, γ-dimethylallylflavone (1).